2010
DOI: 10.1679/aohc.73.23
|View full text |Cite
|
Sign up to set email alerts
|

The initial process of enamel prism arrangement and its relation to the Hunter-Schreger bands in dog teeth

Abstract: belt-like zones, corresponding to the parazone or the diazone of the Hunter-Schreger bands.Reversed images of scanning electron-micrographs of the exposed surfaces of the developing enamel revealed round and bulb-like profiles of Tomes' processes at early amelogenesis and its changes into a characteristic structure combined with flat secretory and enclosing nonsecretory faces that dictated the orientation of corresponding enamel prisms.The results suggest that the groups of enamel prisms oriented in sideward d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 30 publications
2
22
0
1
Order By: Relevance
“…Furthermore, they noticed that there were no statistically significant differences between bracket debonding strength seven days after the bleaching 4 . The same findings were established in the studies conducted by Bishara and Bulut, which showed that if bonding procedure on the bleached teeth was delayed for 1 week the bond strength will increase 1820 . However, Akin et al .…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, they noticed that there were no statistically significant differences between bracket debonding strength seven days after the bleaching 4 . The same findings were established in the studies conducted by Bishara and Bulut, which showed that if bonding procedure on the bleached teeth was delayed for 1 week the bond strength will increase 1820 . However, Akin et al .…”
Section: Discussionsupporting
confidence: 82%
“…It has been associated most often with multiserial enamel where large groups of rods having the same rod angulations spiral, twist or zigzag around one another (Rensberger & von Koenigswald, ; Sahni, ; von Koenigswald & Pfretzschner, ; Hanaizumi et al. , ; Stefen & Rensberger, ; Jiang et al. ; Tabuce et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the past half century, the shape and arrangement of enamel rods have also been of special interest as potential indicators of the pathways ameloblasts follow in secreting the enamel layer (Boyde, ; Osborn, ; Warshawsky, ; Risnes, ; Radlanski & Renz, ; Hanaizumi et al. ; Cox, ; Alloing‐Séguier et al. , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of HSBs has been hindered by technical difficulties. In most cases the analysis HSBs is performed by the use of scanning electron microscopy or polarizing light microscopy in fractured or sectioned teeth (Hanaizumi, Yokota, Domon, Wakita, & Kozawa, ; Leece et al, ; Lynch, O'Sullivan, Dockery, McGillycuddy, & Sloan, ). Invasive or destructive procedures can cause irreversible damage and may not be performed in specimens belonging to private collections, especially if specimens are valuable or unique (Koenigswald et al, ).…”
Section: Introductionmentioning
confidence: 99%